Evidentiary Value of Confession in Trial - Kumar, Navin (CV. Era Digital Nusantara, 2024)
The principle objective of the Indian Evidence Act is to specify the method and documents which the concerned parties in the proceeding to bring and prove before the court. And if any of party fails to prove a particular fact then the court pronounce the verdict against the party, whose onus is to prove it. The Evidence Act clearly mentioned that the hearsay evidence must not be admitted in suit or proceeding generally. But there are certain exceptions to this principle, for example; res gestae, admission, dying declaration, confession etc. Confession is the sub species of admission and mainly includes those statements which suggest or inference the criminal act by the accused. The term confession is nowhere defined in the Evidence Act but the judiciary evolved the idea through the landmark judgements and through the definition of admission. Confession is a statement in which a person or accused pleads guilty. However there are some cases in which the question was raised on the evidentiary value of confession. For instance can the court convict the accused solely on the basis of confession? What confession would be free and involuntary in respect of conviction or acquittal? And if the confession is given the police in custody, whether it would be relevant or not. In this paper, I will discuss the types of confession; to whom the confession made? And what would be the consequences of it?